EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN ROUNDTABLE TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI AKTUALISASI DIRI SISWA SMP NEGERI DI KABUPATEN MAGELANG - Agnes Reswari Ingkansari; Mardiyana Mardiyana; Budi Usodo (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of this research was to determine the effects of learning models on mathematics achievement viewed from the students’ self-actualization. The learning models compared were conventional model, cooperative learning model NHT type and RoundTable type. The type of this research was quasi-experimental research. The population was the 8th grader students of the state junior high school in Magelang regency on academic year 2012/2013. The instruments used were mathematics achievement test and questionnaire. The data were analyzed using unbalanced two way ANOVA. The research conclude as follows. (1) Students’ mathematics achievement using cooperative learning model with Roundtable type, have better students’ mathematics achievement than the ones who use both cooperative learning model with NHT type and conventional learning model, while students mathematics achievement using either NHT or conventional learning model showed similar good result.(2) Students’ mathematics achievement of students who have a high self-actualization is better than students who have both medium and low self-actualization while students who have either medium and low self-actualization have similar good mathematics achievement. (3) In the conventional learning models and cooperative learning model with NHT type, students who have high, medium and low self-actualization have similar mathematics achievement. While in the RoundTable cooperative learning model, students who have high self-actualization produce better mathematics achievement than students who have medium and low self-actualization while either students who have medium self-actualization or students who have low self-actualization have similar good mathematics achievement. (4) On students with high levels of self-actualization, the students’ mathematics achievement using RoundTable type of cooperative learning have better students’ mathematics achievement than by using conventional learning models while by using either NHT type of cooperative learning or conventional learning models produce the similar good mathematics achievement. However, the students who have medium and low self-actualization by using conventional learning model, cooperative learning model NHT and RoundTable have similar good mathematics achievement. Keywords: Self-actualization, Cooperative Learning, NHT, RoundTable.